Una nueva mirada a los asentamientos informales, caso de estudio comuna 14, sector Morrorico. Bucaramanga, Santander - Ávila Rondón, Tatiana Alejandra; Liñán Gómez, Miguel Ángel (Universidad Antonio Nariño, 2022)
This research work addressed the issue of informal settlements in search of a new approach, because these places are seen as something negative in the cities and they have political,